Sensor array made with nanostructured films to detect a phenothiazine compound - Aoki, P. H. B. [UNESP]; Caetano, Wilker [UNESP]; Volpati, D. [UNESP]; Riul, A.; Constantino, C. J. L. [UNESP] (Amer Scientific Publishers, 2008)
The detection of trace amounts of phenothiazines with fast, direct methods is important for medical applications and the pharmaceutical industry. In this paper we explore the concept of an electronic tongue to detect methylene blue (MB), with a sensor array comprising 6 units. These units were a bare Pt electrode, and Pt electrodes coated with 1-layer LB films of dipalmitoyl phosphatidylcholine (DPPC) and dipalmitoyl phosphatidylglycerol (DPPG), a 5-layer LB film of stearic acid, and 10 nm PVD films of bis benzimidazo perylene (AzoPTCD) and iron phthalocyanine (FePc). The electrical response obtained with impedance spectroscopy varied with the sensing unit, in spite of the small film thickness, thus indicating good cross-sensitivity. Upon treating the capacitance data at 1 kHz with Principal Component Analysis (PCA), the sensor array was capable of distinguishing MB solutions from ultrapure water down to 1 nM. This unprecedented high sensitivity was probably due to strong interactions between MB and DPPC and DPPG, as the sensing units of these phospholipids gave the most important contributions to the PCA plots. Such strong interaction was not manifested in the surface pressure-area isotherms of co-spread monolayers of MB and DPPC or DPPG, which emphasizes the high sensitivity of the electrical measurements in ultrathin films in contact with liquids, now widely exploited in electronic tongues.
Keywords: Phospholipids; Phenothiazine; Sensors